Association of Characteristics, Deficits, and Outcomes of Residents Placed on Probation at One Institution, 2002–2012. (March 2016) - Guerrasio, Jeannette; Brooks, Elizabeth; Rumack, Carol M.; Christensen, Alicia; Aagaard, Eva M.
Abstract : Purpose: To describe the population of residents placed on probation, identify learner characteristics associated with being placed on probation, and describe immediate and long-term career outcomes for those placed on probation as compared with matched controls. Method: The authors collected data for residents at the University of Colorado School of Medicine placed on probation from July 2002 to June 2012, including postgraduate year placed on probation, deficits identified, mandated evaluation for physical and mental health, duration of probation, disability accommodations requested, and number of additional training months required. They were retrospectively compared with 102 controls matched for specialty, matriculation, and postgraduate year. Variables assessed included demographics, academic performance, license status, specialty, state board certification, and board citations. Results: Of 3, 091 residents, 3.3% were placed on probation (88 residents; 14 fellows). Compared with controls, those on probation were more likely to be international medical graduates, married, not Caucasian, older (all P < .001), male ( P = .01), to have transferred from another graduate medical education training program, and to have taken time off between medical school and residency (all P < .001). Among those currently in practice, 53 (63.9%) were board certified compared with 93 (100%) of the controls. Placement on probation was associated with failure to graduate and lack of board certification. All 7 graduates cited by state medical boards were in the probation group. Conclusions: Further research is needed to understand these associations and to determine whether changes in curricula or remediation programs may alter these outcomes.